PERMINTAAN BERAS DI PROPINSI JAWA TIMUR - Aron, Robertus; Pudjiastuti, Agnes Quartina; Sa'diyah, Ana Arifatus (Universitas Tribhuwana Tunggadewi, 2019)
This study aims to analyze the demand for rice in East Java. Demand of rice in East Java Province was collected from BPS and analyzed using multiple linear regression. Coefficient of determination (R2) resulting from this method amounted to 0.477 that meaning was 48% of demand of rice in East Java Province was explained by rice prices, corn prices, sweet potato prices, cassava prices, and per capita income. The remaining (52%) was explained by other variables other than methods such as population, consumer tastes, price of other foods. Demand of rice was influenced by price of rice, price of corn, and income per capita. Penelitian ini bertujuan untuk menganalisis permintaan beras di Jawa Timur. Data permintaan beras di Propinsi Jawa Timur diperoleh dari Badan Pusat Statistik (BPS) tahun 2016 dan dianalisis menggunakan regresi linier berganda. Koefisien determinasi (R2) yang dihasilkan dari metode ini sebesar 0.477. artinya 48% permintaan beras di Propinsi Jawa Timur dijelaskan oleh harga beras, harga jagung, harga ubi jalar, harga ubi kayu, dan pendapatan per kapita. Sisanya sebesar 52% dijelaskan oleh variabel lain di luar model permintaan beras seperti jumlah penduduk, selera konsumen, harga bahan pangan lain. Pemintaan beras di Propinsi jawa Timur dipengaruhi oleh harga beras itu sendiri, harga jagung, dan pendapatan perkapita.